Happiness and Spinal-Cord Injury: A Journey Through Traditions of Virtue to Positive Psychology - Clifton, Shane (Journal of religion, disability & health, 2013)
This article has its motivation in the experience of its author who, following a serious accident, was rendered a quadriplegic. It explores the potential contribution of the virtue tradition to the happiness of people with a spinal-cord injury. Drawing on the philosophical insights of Aristotle, Aquinas, and Alistair MacIntyre, it connects the virtue tradition to the more recent psychological science of positive psychology, and shows how the emerging conception of happiness can speak to the challenge of living with an acquired disability. It identifies the impact of spinal cord injury on a person's capacity to experience bodily pleasure, but goes on to argue that the pursuit of meaning and the exercise of virtue enables a more substantive happiness—better understood as well-being. It concludes by identifying some of the virtues needed to negotiate dependence on carers while, at the same time, achieving as much independence as possible.